Fields of Plenty, Fields of Lean: The Early Labour Market Outcomes of Canadian University Graduates by Discipline - Finnie, Ross (Canadian Journal of Higher Education, 2001)
This paper reports the results of an empirical analysis of the early career outcomes of recent Canadian Bachelor's level graduates by discipline based on three waves of the National Graduates Surveys, which comprise large, representative databases of individuals who successfully completed their programmes at Canadian universities in 1982, 1986, and 1990, with information gathered during interviews conducted two and five years after graduation for each group of graduates (1984-87, 1988-92, 1990-95). Many outcomes conform to expectations, typically reflecting the different orientations of the various disciplines with respect to direct career preparedness, with the professions and other applied disciplines generally characterised by lower unemployment rates, closer skill and qualification matches, higher earnings, and so on. On the other hand, while the "applied" fields also tend to perform well in terms of the more subjective measures regarding job satisfaction and the overall evaluation of the chosen programme, these outcomes also depart from what job market outcomes alone might have predicted (e.g., fine arts and humanities graduates are more satisfied than many others). Some implications of the findings are discussed and avenues for future research are suggested.